Influence of dialysis duration and parathyroid hormone on the clinical and radiographic oral conditions of pre-transplant patients with chronic kidney disease - Queiroz, Stênio Medeiros (2015)
Aim: To evaluate the oral conditions of patients with chronic kidney disease undergoing dialysis and to determine the influence of dialysis duration and bone metabolism on the prevalence and severity of the alterations found. Methods: The simplified oral hygiene index (OHI-S), prevalence of dental caries (decayed, missing filled teeth index, DMFT), and the periodontal screening and recording (PSR) index were evaluated in 154 patients. Parathyroid hormone (PTH), calcium, phosphorus and urea measurements, as well as panoramic radiographs, were obtained from all patients. To evaluate the effect of duration of dialysis treatment on oral health, the patients were divided into two groups: (1) <5 years and (2) > 5 years. Regarding blood levels of PTH, patients were divided into three groups: (1) 0-149 pg/mL, (2) 150-584 pg/mL, and (3) >585 pg/mL. The OHI-S identified the accumulation of biofilm and calculus around the teeth. Results: Gingival inflammation was found in 100% of dentate patients, with 2 being the predominant PSR score (72.3%). The DMFT index was high (17.52). Dental calculus was the most common radiographic finding (70.8%). No significant correlation was observed between dialysis duration, biochemical alterations, and oral health. Conclusions: Most patients undergoing dialysis presented precarious oral hygiene, periodontal inflammation, and bone alterations. However, these manifestations were not influenced by the duration of dialysis or bone metabolism.